Aminocarbonylation of aryl iodides with primary and secondary amines in aqueous medium using polymer supported palladium-N-heterocyclic carbene complex as an efficient and heterogeneous recyclable catalyst - Qureshi, Ziyauddin S.; Revankar, Santosh A.; Khedkar, Mayur V.; Bhanage, Bhalchandra M. (Catalysis today, 2012)
An efficient phosphine-free protocol for the aminocarbonylation of aryl iodides with primary and secondary amines using PS-Pd-NHC complex as a heterogeneous and recyclable catalyst has been developed. The developed protocol is more advantageous due to use of water as environmentally benign solvent and effective catalyst recyclability. [Display omitted] ► A highly efficient phosphine free PS-Pd-NHC catalytic system for aminocarbonylation reaction of aryl iodides with primary and secondary amines was developed in aqueous medium. ► General applicability of the developed protocol was investigated. ► The developed protocol is advantageous due to use of water as environmentally benign solvent. ► The catalyst exhibited remarkable recyclability for four consecutive cycles. Aminocarbonylation of aryl iodides with primary and secondary aromatic/aliphatic amines to corresponding amides using polymer supported palladium-N-heterocyclic carbene complex (PS-Pd-NHC) as an efficient heterogeneous, recyclable catalyst is described. The catalytic system was optimized with respect to various reaction parameters to give excellent yield of desired products. The catalyst can be easily separated by simple filtration process and recycled further up to four consecutive recycle without loss in any activity and selectivity. The protocol is advantageous due to the ease in handling of the catalyst, simple workup procedure, and environmentally benign water as solvent and effective catalyst recyclability.